Розробка та дослідження мобільного додатка для нагадування про приймання ліків - Шворак, Дмитро Михайлович (Луцьк : ЛНТУ, 2025)
Робота присвячена розробці мобільного додатка для планування прийому ліків, відправки сповіщень користувачу, збереження історії лікування та перегляду статистики виконання. Проаналізовано предметну область, обґрунтовано вибір технологій і реалізовано функціональну систему, яка відповідає поставленим вимогам.

The thesis focuses on the development of a mobile application for scheduling medication intake, sending notifications, storing treatment history, and viewing usage statistics. The subject area was analyzed, the technology stack was justified, and a functional system was implemented that meets the specified requirements.
Development and research of a mobile application for reminding about taking medication
Keywords: Android; Kotlin; Jetpack Compose; Room; AlarmManager; інформаційна система